Ginseng intake and Alzheimer disease-specific cognition in older adults according to apolipoprotein ε4 allele status - Lee, Boung Chul; Choe, Young Min; Suh, Guk-Hee; Choi, Ihn-Geun; Kim, Hyun Soo; Hwang, Jaeuk; Yi, Dahyun; Jhoo, Jin Hyeong; Kim, Jee Wook (Frontiers in Aging Neuroscience, 2023)
Background The probable association among ginseng intake, Alzheimer’s disease (AD)-specific cognition, and apolipoprotein ε4 (APOE4) remains poorly investigated. Hence, we examined the association between ginseng intake and AD-specific cognition in older adults under the moderating effect of APOE4 status. Methods This study enrolled 160 adults aged 65–90 years without dementia. All participants underwent comprehensive dietary and clinical assessments including ginseng intake, AD-related cognition (i.e., delayed episodic memory, as the earliest cognitive change in AD), and non-memory cognition for comparative purposes. Results Ginseng intake was associated with higher delayed episodic memory, but not non-memory cognition, compared to no ginseng intake. The interaction between ginseng intake and APOE4 status had a significant effect on delayed episodic memory. Subgroup analyses showed that ginseng intake was associated with higher delayed episodic memory in the APOE4-negative but not the APOE4-positive subgroup. The benefits of ginseng intake on delayed episodic memory were prominent in the high duration (≥5 years) and midlife onset (<65 years) groups. Conclusion Our study of older adults with no dementia suggests that ginseng intake (with high duration and midlife onset) had a beneficial effect on AD-specific cognitive decline, i.e., the delayed episodic memory. In addition, APOE4 status moderates the association between ginseng intake status and AD-specific cognitive decline.